1986
DOI: 10.1002/app.1986.070310205
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Tri‐O‐alkylcellulose by the use of a nonaqueous cellulose solvent and their physical characteristics

Abstract: SynopsisTri-0-methyl-, ethyl-, -n-propyl-, -n-butyl-, -n-pentyl-, -iso-amyl-, -n-hexyl-, -n-heptyl-, -n-octyl-, -n-decyl-, and -3-phenoxypropylcelluloses have been prepared with powdered sodium hydroxide and the corresponding alkyl iodides or bromides in one of nonaqueous cellulose solvents, SO2 -diethylamine-dimethylsulfoxide. These new tri-0-alkylcelluloses were characterized by infrared spectra, I3CNMR spectra, and optical rotations. The first six tri-0-alkylcelluloses described above were obtained as white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…Thus, of great interest is the application of cellulose as a precursor for chemical modification leading to various types of cellulose derivatives, such as the nitrate [1], ester [2][3][4], ether [5][6][7], and carbamate [8][9] of cellulose. In addition, carboxymethyl cellulose (CMC), the most important ionic cellulose ester, is widely used as building material additives, printing inks, coatings, pharmaceuticals, food, cosmetics, paper or textiles [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, of great interest is the application of cellulose as a precursor for chemical modification leading to various types of cellulose derivatives, such as the nitrate [1], ester [2][3][4], ether [5][6][7], and carbamate [8][9] of cellulose. In addition, carboxymethyl cellulose (CMC), the most important ionic cellulose ester, is widely used as building material additives, printing inks, coatings, pharmaceuticals, food, cosmetics, paper or textiles [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Trityl cellulose was alkylated according to a procedure similar to that described by Isogai et al (10). Approximately 7-10 g of hityl cellulose was added to 300 mL of dry DMSO and allowed to dissolve.…”
Section: Methodsmentioning
confidence: 99%
“…The polymers 6-0-trityl-2,3-0-butyl cellulose (TBuC), 6-0-trityl-2,3-0-pentyl cellulose (TPeC), and 6-0-trityl-2,3-0-hexyl cellulose (THeC) were synthesized from trityl cellulose using a procedure similar to that described by Isogai et al (10). These workers found that cellulosic hydroxyl groups can be alkylated by reacting cellulose, dissolved in a SO2-DEA-DMSO solvent system, with sodium hydroxide and an appropriate alkyl iodide.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Fig . 2 shows that crystallinities of cellulose I of GWP and TMP were decreased with the increase in the amount of S0 2-DEA added, but the complete All hydroxyl groups in cellulose react with S02 DEA to form a special complex between them when it is dissolved in the S02-DEA-DMSO system [16). Dur ing this reaction, all intra and inter-molecular hy drogen bonds in cellulose are completely cleaved.…”
Section: Analysesmentioning
confidence: 98%